Prosody and iconicity. - Hancil, Sylvie (Iconicity in language and literature., 2013)
The benefit of prosodic and additional spectral over exclusively cepstral feature information is investigated for the recognition of phonemes in eight different speaking styles reaching from informal to formal. As prosodic information is best analyzed on a supra-segmental level, the whole temporal context of a phoneme is exploited by application of statistical functionals. 521 acoustic features are likewise obtained and evaluated per descriptor and functional by either de-correlating floating search feature evaluation or classification performance: The classifier of choice are Support Vector M.